Interaction of Emotion and Cognition in the Processing of Textual Material - Davou, Bettina (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractCognitive psychology and cognitive science have only recently come to acknowledge that human beings are not “pure” cognitive systems, and that emotions may be more than simply another form of cognition. This paper presents recent theoretical issues on the interaction of cognition with emotion, drawing on findings from evolutionary, neurobiological and cognitive research. These findings indicate that emotions have a fundamental and, often, universal importance for human cognitive functioning. Advanced cognitive processing, such as the processing required for text comprehension and translation, most of the time follows after a first, primary appraisal of the emotional impact of the information on the reader. This type of appraisal is momentary, non-conscious and non-cognitive, and is carried out by some system in the organism that functions with its own distinctive rules, different from those of the cognitive system. Emotional appraisal of the information sets the mode in which the organism (including its cognitive processes) will operate. Evidence suggests that negative emotions can instantly and non-consciously increase processing effort and time and decrease cognitive capacity, while on the other hand, positive emotions generally increase cognitive resources and expand attention and creativity. This implies that both cognitive processing of textual information, as well as its outcome, are influenced not only by the interpreters cognitive skill or by the emotional features of the text per se (the emotional impact that the writer has attempted to generate), but also (and perhaps most importantly) by the subjective emotional significance that the information has for each individual interpreter.